Settlement Analysis of Soil Replaced with Fine Aggregate of Recycled Concrete as Foundation Material - Kumar, A. Raj; Bhushan, J. Y. V. Shiva (Novel Perspectives of Engineering Research Vol. 9, 2022)
One of the most common waste items generated by the construction industry is Crushed Concrete (CC). This material is commonly recycled and utilized for a variety of purposes, including pavement, concrete aggregates and backfilling. The objective of this study is to check the potentiality of Crushed concrete- Fine Aggregate (CC-FA) blended soils as a foundation material. Recycled concrete is collected from demolished buildings in Secunderabad and sorted by gradation. The index properties of CC-FA such as pH, specific gravity, water absorption, and particle size distribution are obtained. Locally available soil is partially replaced, i.e., 30%, 50%, and 70% with CC-FA, and its compaction and shear strength parameters are ascertained. In continuation to the study, a numerical analysis is performed using finite element software i.e., GeoStudio Sigma/w. Mesh and boundary extent convergence studies are done for the model. The top 1 m virgin soil is replaced with mixture of CC-FA and soils. Settlements for various percentages of CC-FA and different widths of square footing are obtained for uniform stress of 200kPa. To simulate real-field conditions, the stress is applied in five stages. It was discovered that 30% replacement of CC-FA resulted in least settlement for all footing widths considered in this research.